2021
DOI: 10.1158/0008-5472.can-20-2052
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 and E2F2-Mediated Repression of CPT2 Establishes a Lipid-Rich Tumor-Promoting Environment

Abstract: Lipid metabolism rearrangements in nonalcoholic fatty liver disease (NAFLD) contribute to disease progression. NAFLD has emerged as a major risk for hepatocellular carcinoma (HCC), where metabolic reprogramming is a hallmark. Identification of metabolic drivers might reveal therapeutic targets to improve HCC treatment. Here, we investigated the contribution of transcription factors E2F1 and E2F2 to NAFLD-related HCC and their involvement in metabolic rewiring during disease progression. In mice receiving a hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Although the E2Fs pathway is often deregulated in cancer, the roles of E2F1 as a proliferation or cell death promoter in tumorigenesis are still far from being understood [ 33 , 34 ]. Numerous studies indicate that E2F1 transcription factor is one of the most in-depth E2Fs family members in tumor research, and the high expression of E2F1 is of great significance for the poor prognosis of malignant tumors such as gastric cancer [ 35 ], hepatocellular carcinoma [ 36 ], pancreatic cancer [ 37 ], and prostate cancer [ 38 ]. Ma et al [ 9 ] have first reported that the mRNA level of E2F1 in renal clear cell carcinoma tissue is related to tumor pathological parameters, including diameter, Fuhrman tumor grade, pT staging, TNM staging and macrovascular infiltration (MAVI), and E2F1 expression with the increase of tumor tissue grade; they also found that E2F1 has promoting effects on the proliferation, migration, and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the E2Fs pathway is often deregulated in cancer, the roles of E2F1 as a proliferation or cell death promoter in tumorigenesis are still far from being understood [ 33 , 34 ]. Numerous studies indicate that E2F1 transcription factor is one of the most in-depth E2Fs family members in tumor research, and the high expression of E2F1 is of great significance for the poor prognosis of malignant tumors such as gastric cancer [ 35 ], hepatocellular carcinoma [ 36 ], pancreatic cancer [ 37 ], and prostate cancer [ 38 ]. Ma et al [ 9 ] have first reported that the mRNA level of E2F1 in renal clear cell carcinoma tissue is related to tumor pathological parameters, including diameter, Fuhrman tumor grade, pT staging, TNM staging and macrovascular infiltration (MAVI), and E2F1 expression with the increase of tumor tissue grade; they also found that E2F1 has promoting effects on the proliferation, migration, and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) analysis in isolated hepatocytes were performed as describe before 58 . Briefly, after hepatocytes isolation and attachment, crosslinking were directly performed on the culture plates by addition of formaldehyde to a 1% final concentration.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that ILF2 can maintain mitochondrial homeostasis, especially oxidative phosphorylation, and promote the progression of small lung cancer via interacting with E2F1, which is a key transcriptional activator involved in the modulation of mitochondrial functions ( Zhao et al, 2019 ). Notably, recent studies have indicated that E2F1 and E2F2 regulate the expression of CPT2, an important enzyme for FA β-oxidation, and establish a lipid-rich environment for hepatocarcinogensis ( Gonzalez-Romero et al, 2021 ). Combined with these findings, we proposed that ILF2 might exhibit a close relationship with FA β-oxidation in ESCC.…”
Section: Discussionmentioning
confidence: 99%